Anxiety and Self-Defense Mechanism of the Characters in Maleficent Movie - Rinda Dwi Andini (Prodi Jurnalistik Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
Literature is an art that uses imagination even based on experiences, thoughts, and feelings and uses beautiful language style. This study analyzes anxiety and self-defense mechanisms in two characters in the Maleficent movie, Maleficent and Stefan. This study aims to describe the types of anxiety experienced by the characters and also to explain the self-defense mechanisms used by the characters in dealing with anxiety. This study uses psychoanalysis theory by Sigmund Freud and qualitative descriptive methods to analyze the anxiety and self-defense mechanisms experienced by the characters. The results of the analysis of this study found that Maleficent has one type of anxiety that is realistic anxiety and uses three types of self-defense mechanisms that are displacement, sublimation, and reaction formation. On the other hand, Stefan has two types of anxiety that is realistic anxiety and neurotic anxiety and uses two types of self-defense mechanisms that is displacement and projection. Anxiety and self-defense mechanisms that occur in Maleficent are due to pressure and danger carried out by King Stefan, while anxiety and self-defense mechanisms that occur in King Stefan are due to resistance or attacks and threats of danger by Maleficent